Minimum number of Weyl point phonons in mixed-metal periodate RbGeIO6 - Yang Li (Results in Physics, 2023)
In topology physics, the prediction of Weyl systems with the minimum nonzero number of Weyl points (WPs) remains challenging. In this study, for the first time, we propose the P312 type RbGeIO6 as a material candidate with the minimum number of WPs in its phonon curves. Based on first-principles calculations and symmetry analysis, we confirm that the RbGeIO6 exhibits only two charge-two (C-2) WPs at the Γ and A time-reversal-invariant momenta points in the 3D Brillouin zone (BZ). Furthermore, the two C-2 WP phonons at the Γ and A result in the formation of the clean and long phononic double surface state on the (010) surface. The phononic double surface state spans the entire first surface BZ of the (010) surface, facilitating their detection in future experimental studies.